Reviewing the association between motor competence and physical activity from a behavioral genetic perspective - Zi, Yahua; de Geus, Eco J. C. (Frontiers in Psychology, 2025)
A much-cited model by Stodden and colleagues has proposed motor competence to be a 17 promising target for intervention to increase childhood physical activity. Motor competence is thought to influence future physical activity through bidirectional causal effects that are partly direct, and partly mediated by perceived motor competence and physical fitness. Here, we argue that the model is incomplete by ignoring potential confounding effects of age-specific and age-invariant factors related to genetics and the shared family environment. We examined 106 systematic reviews and/or meta-analyses on the Stodden model for the mention of familial confounding. These reviews summarized data from 1,344 primary studies on children in the age range 0–18 on the associations in five bidirectional pathways: motor competence—physical activity, motor competence—perceived motor competence, perceived motor competence—physical activity, motor competence—physical fitness, and physical fitness—physical activity. We show that a behavioral genetic perspective has been completely lacking from this vast literature, despite repeated evidence for a substantial contribution of genetic and shared environmental factors to motor competence (h2 = ♂55%—♀58%; c2 = ♂31%—♀29%), physical fitness (h2 = ♂65%—♀67%; c2 = ♂3%—♀2%), and physical activity (h2 = ♂37%—♀29%; c2 = ♂33%—♀49%). Focusing on the alleged causal path from motor competence to physical activity, we find that the systematic reviews provide strong evidence for an association in cross-sectional studies, but weak evidence of prediction of physical activity by motor competence in longitudinal studies, and indeterminate effects of interventions on motor competence. Reviews on interventions on physical activity, in contrast, provide strong evidence for an effect on motor competence. We conclude that reverse causality with familial confounding are the main sources of the observed association between motor competence and physical activity in youth. There is an unabated need studies on the interplay between motor competence, perceived motor competence, physical fitness, and physical activity across early childhood and into adolescence, but such studies need to be done in genetically informative samples.